Эртний уур амьсгалын өөрчлөлтийг Хөвсгөл нуурын хурдсын элементүүдээр тодорхойлох IСР-МS шинжилгээний арга зүй - Ц.Оюунчимэг, (Geological Issues, 2023)
To obtain high-resolution records of elemental paleo environmental change proxies in bottom sediments of Lake Hovsgol (Mongolia), a high-performance technique is proposed. It consists of extraction of sediment samples with 1 % HNO3 followed by multi-elemental ICP-MS measurements of extracts. In comparison with the complete decomposition of bulk samples, this method provides maximal number (44) of climate-sensitive elemental signals (variation of contents of extractable elements along sediment core depth) and. at the same time, their maximal response to the global paleoclimate change. The most sensitivity to climate change is characteristic for Cinorg. P, Ca, V, Ni, Se, Br, Sr, Mo, Sb. I, W and U, and the minimal one (25-30 %) - for As, Rb and Pb. On the base of memory effect studies, an algorithm of ICP-MS measurement is proposed: this method does not require intermediate rinsing of spectrometer measuring path between core samples analyzed subsequently. It allows increasing the output of serial analysis up to 200 samples per day.